Comparative study of angioplastic patches. - Pomatta, José; Burghi, Gustavo; Mauro, Carlos; Siécola, Osvaldo; Gastambide, Carmelo; Gravina, Francisco (Cirugía del Uruguay, 1988)
The lncldence ol restenosls after carotid endarterec• tomy Is very low, varylng between 1,2% and 3.6% after 7 months to 2 years. In 25% of the cases Intima! hyper• plasla was found. The aims of this experimental study are to a) create a model of carotld stenosls in dogs b) study the difieren! types ol angloplasty (veln and poly• tetralluoroethylene patches) and c) clarify the lesiona! mechanism that causes stenosis.